Female heterogamety and extraordinary low chromosome number in Rana paramacrodon (Amphibia: Ranidae) - H. S., Yong; K. L., Ng (Malaysian Journal of Science, 1994)
The karyotypes of a male and two female specimens ofRanaparamacrodon from Singapore were examined. The diploid number of 2N=20 is the lowest known for the genus Rana. All the ch-romosomes were biarmed. The female frog was heterogametic (with ZW sex chromosomes), while the male was homogametic (ZZ). Autosome pair no. 1 was distinctly longer than the rest. The smallest autosome pair was also distinctive in size, morphology and the presence of a secondary constriction on the long arm. ABSTRAK Kariotip Rana paramacrodon telah dikaji atas seekor katak jantan dan dua ekor katak betina dari Singapura. Nombor diploid dengan 2N=20 adalah yang paling rendah bagi genus Rana. Setiap kromosom mempunyai dua lengan. Katak betina adalah heterogametik (dengan kromosom seks ZW), manakala katak jantan adalah homogametik (ZZ). Panjang pasangan autosom no. 1 berbeza dengan nyatanyadaripadakromosom-kromosom yang lain. Pasangan autosom terkecil adalah juga distinktif dalam saiz, morfologi dan kewujudan cerutan sekunder pada lengan panjang. (karyotype, female heterogamety, Rana paramacrodon, Amphibia, Anura)